Viralité et résistance aux discours de haine - Béatrice Turpin (MediAzioni)
Virality plays on the emotion that drives people to quickly retransmit a message, without really analysing it or subjecting it to criticism. The more emotional the message is, the more appropriate it seems to go viral, which is one of the premises of viral marketing. This explains the virality of violent content on the Internet. From this pint of view can the fight against hate speech use virality when its aim is to call for reflection? We show that virality can serve as a catalyst for reflection, and that emotion can also be positive (Danblon, 2013). From this point of view, we take a look at the Council of Europe's Youth Campaign against Hate Speech, which uses social media to bring together and share in a community also made up of real-life interactions. We then analyse more particularly some visuals, memes, a community semiotic form which allows to start from emotions to reflect on the stereotypes which underlie hate speech.